H3K4 Methyltransferase Set1a Is A Key Oct4 Coactivator Essential for Generation of Oct4 Positive Inner Cell Mass. (19th January 2016) - Fang, Lan; Zhang, Jun; Zhang, Hui; Yang, Xiaoqin; Jin, Xueling; Zhang, Ling; Skalnik, David G.; Jin, Ying; Zhang, Yong; Huang, Xingxu; Li, Jiwen; Wong, Jiemin
Abstract: Limited core transcription factors and transcriptional cofactors have been shown to govern embryonic stem cell (ESC) transcriptional circuitry and pluripotency, but the molecular interactions between the core transcription factors and cofactors remains ill defined. Here, we analyzed the protein–protein interactions between Oct4, Sox2, Klf4, and Myc (abbreviated as OSKM) and a large panel of cofactors. The data reveal both specific and common interactions between OSKM and cofactors. We found that among the SET1/MLL family H3K4 methyltransferases, Set1a specifically interacts with Oct4 and this interaction is independent of Wdr5. Set1a is recruited to and required for H3K4 methylation at the Oct4 target gene promoters and transcriptional activation of Oct4 target genes in ESCs, and consistently Set1a is required for ESC maintenance and induced pluripotent stem cell generation. Gene expression profiling and chromatin immunoprecipitation-seq analyses demonstrate the broad involvement of Set1a in Oct4 transcription circuitry and strong enrichment at TSS sites. Gene knockout study demonstrates that Set1a is not only required for mouse early embryonic development but also for the generation of Oct4-positive inner cell mass. Together our study provides valuable information on the molecular interactions between OSKM and cofactors and molecular mechanisms for the functional importance of Set1a in ESCs and early development. Abstract : Set1a is a key Oct4 coactivator that is required for ESC maintenance, efficient induction of iPS cells, formation of Oct4 positive inner cell mass and early embryonic development. (A): Set1a interacts with Oct4 and is required for transcriptional activation of Oct4 positively regulated genes in ES, Oct4 positive inner cell mass and iPS cells. (B): Diagrams illustrating that Set1a is highly expressed in ES cells, Oct4 positive inner cell mass and iPS cells. Reduced Set1la expression correlates with cell differentiation and Set1a knockout results in mouse early embryonic death with loss of Oct4 positive inner cell mass.